(3eSGFd GdSeGSQI aj GdHjhYs - (3YHO Gddg Hf CMeO Hf EHQGgje, GdJhfSjs
(3ChdgG (B:s
(3SCdJ CHG GdYHGS YHO Gddg Hf CMeO Hf EHQGgje hdGHjGfi QMeg Gddg s
(3BNQgG (B:s
(3GfJLY Edi efGO BNQ ajHjYg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B(33(3c(B) s
Keywords: (3CUhd Gdabgs